Insights into interactions of flavanones with target human respiratory syncytial virus M2-1 protein from STD-NMR, fluorescence spectroscopy, and computational simulations - Piva, Hêmily M. R. [UNESP]; Sá, Jéssica M. [UNESP]; Miranda, Artemiza S. [UNESP]; Tasic, Ljubica; Fossey, Marcelo A. [UNESP]; Souza, Fátima P. [UNESP]; Caruso, Ícaro P. [UNESP] (MDPI, 2020)
The human Respiratory Syncytial Virus (hRSV) is the most frequent agent of respiratory infections in infants and children with no currently approved vaccine. The M2-1 protein is an important transcriptional antitermination factor and a potential target for viral replication inhibitor development. Hesperetin (HST) and hesperidin (HSD) are flavonoids from the flavanone group, naturally found in citrus and have, as one of their properties, antiviral activity. The present study reports on the interactions between hRSV M2-1 and these flavanones using experimental techniques in association with computational tools. STD-NMR results showed that HST and HSD bind to M2-1 by positioning their aromatic rings into the target protein binding site. Fluorescence quenching measurements revealed that HST had an interaction affinity greater than HSD towards M2-1. The thermodynamic analysis suggested that hydrogen bonds and van der Waals interactions are important for the molecular stabilization of the complexes. Computational simulations corroborated with the experimental results and indicated that the possible interaction region for the flavonoids is the AMP-binding site in M2-1. Therefore, these results point that HST and HSD bind stably to a critical region in M2-1, which is vital for its biological function, and thus might play a possible role antiviral against hRSV.
Keywords: Flavanones; Fluorescence spectroscopy; HRSV M2-1; Molecular docking; Molecular dynamics; STD-NMR